EFEKTIVITAS PEMUNGUTAN PAJAK KENDARAAN BERMOTOR MELALUI LAYANAN SAMSAT KELILING BAPENDA PROVINSI RIAU - Agung Priyatna; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
BAPENDA Riau Province Mobile Samsat Program is a manifestation of current technological developments. The Mobile Samsat program is a flagship program owned by BAPENDA Riau Province. The Mobile Samsat Program is a motor vehicle tax payment service (PKB) using the ball pick-up method to make it easier and improve services to people who will pay motorized vehicle taxes. The purpose of this study is to determine the effectiveness of motor vehicle tax collection through the mobile social security services of BAPENDA Riau Province and to determine the factors that support the effectiveness of motor vehicle tax collection through the mobile social security services of BAPENDA Riau Province. This study uses purposive sampling technique and qualitative research uses a descriptive approach and uses data collection techniques by means of observation, interviews and documentation and for further analysis. The results of this study indicate that: first, the traveling Samsat program has been effective. Second, the supporting factors of this traveling Samsat program are  socialization, community trust, service location. Keywords: program effectiveness, motor vehicle tax, service